Written production in French language learning (Humanities, Technology and Education Journal, 2025)
The purpose of the study was to analyze the written production process in learning French as a foreign language (FLE) in a group of B1.2 level students at a Colombian public university. Using a qualitative approach and case study, non-participatory observations, interviews, and analysis of written productions were applied in three different contexts: independent work, classroom activities, and assessments. The theoretical foundations were based on the Common European Framework of Reference for Languages (Council of Europe, 2000) and the contributions of Vigner (2012), Chartrand (1993), Bouchard, and Kadi (2011), among others, who highlight linguistic, sociolinguistic, and pragmatic skills as pillars of the writing process. The results show that students recognize written production as an integral skill that combines discursive, linguistic, and sociocultural elements. They also value teacher support, planning, dictionary use, and prior reading as strategies for structuring their texts. Their strengths include coherence, cohesion, and vocabulary management, while their main difficulties are related to grammar, connectors, and error correction. The study highlights the importance of promoting teaching strategies that strengthen autonomy, reflective revision, and systematic writing practice in French language learning.
Keywords: written production; learning French; foreign language; language skills; sociolinguistic competence; pragmatic competence; writing strategies; university teaching